Transparency in Village Fund Management (A Case Study in the Bang Haji Subdistrict, Central Bengkulu Regency) - Hermanto, Bambang Agoes; Antoni; Rospida, Lela (PT FORMOSA CENDEKIA GLOBAL, 2024)
This researcher aims to analyze the transparency of village fund management in Bang Haji District, Central Bengkulu Regency. The sample for the questionnaire was 72 taken using accidental sampling technique. Data analysis in this study used a descriptive test. The results of the study fall into the Medium or Moderate classification, because the village head has not been fully transparent in the Management of Village Funds in Bang Haji District, Central Bengkulu Regency because of information about detailed financial reports both the income budget and the expenditure budget. all programs and activities are not published and cannot be accessed by the public. However, only a few programs and activities are known if community programs and activities are the implementers.